Pliny the Elder themes and contexts - Gibson, Roy K.; Morello, Ruth. (Mnemosyne, Supplements, 2011)
Pliny's Naturalis Historia - a brilliant and sophisticated encyclopaedia of the scientific, artistic, philosophical, botanical and zoological riches of the ancient world - has had a long career in the footnotes of historical studies. This is a phenomenon born of the sense that the work was there to consult, or to 'use', as a resource to aid investigation of specific technical issues or passages, of Quellenforschung, or of delimited topic areas. The contributors to the present volume both represent and join a new generation of critics who have begun to try to 'read' this monumental text, and - by examining the dominant motifs which give shape and order to the work - to construct frameworks within which we may understand and interpret Pliny's overarching agenda.